Inverted planar perovskite solar cells featuring ligand-protecting colloidal NiO nanocrystals hole transport layer. (February 2020) - Liu, Heming; Song, Jian; Qin, Yongshan; Mou, Junpeng; Qiu, Qinyuan; Zhao, Yulong; Zhu, Lei; Qiang, Yinghuai
Abstract: Nickel oxide (NiO) is a promising material to replace organic hole transport materials and solve the stability problem of perovskite solar cells (PSCs). Various methodologies have been applied to synthesize high quality NiO, especially for colloidal nanocrystals (NCs) route, which well behaves in the nanocrystals synthesis field. To better introduce this route to the perovskite solar cell field and produce well-performance hole transport layers (HTLs) of NiO NCs, we got inspired by ligand-protecting strategy. The stability of NiO NCs in reaction system is improved significantly, and the nucleation and growth of NiO NCs can be controlled effectively, which makes for the high crystallinity. Furthermore, the extraordinary dispersion of NiO NCs in chlorobenzene solvent can be observed, which makes the preparation of HTL films by simple spin-coating method possible. The relevant measurements and analysis manifest that the HTLs of NiO NCs with excellent transparency, good film-forming performance, admirable hole transport capability and few interface traps can be obtained by optimizing the concentration of NiO NCs, finally contributing to the photovoltaic performance of corresponding inverted planar PSCs. Our work broadens the application of colloidal chemical synthetic route in PSCs field and highlights the superiority of this protocol further. Highlights: A well-dispersed NiO NCs in chlorobenzene was prepared by noninjection method. A dense NiO film was fabricated using the prepared NiO by simple spin-coating method. The interface charge transfer property of PSC using this NiO film were investigated.